Cavas históricas de ouro do Jaraguá: o que resta para se preservar? - Dal Ré Carneiro, Celso; Dos Santos, Luiz Fernando; Da Silva, José Reynaldo Bastos [UNESP] (My University, 2011)
The Historical Jaraguá Gold Caves are vestiges of excavations in weathered rock, dating back to the Brazilian colonial times, situated NW of Jaraguá peak, in the São Paulo municipality (SP). The areas were investigated to support historical preservation innitiatives. The excavations have lateral steep slopes and a narrow fat bottom zone, occupied by dense vegetation. The trace of the excavations is sinuous, trending N40-50W, in accordance to a transition zone of Neoproterozoic rocks: metapelites and metapsamites by the SW side and calc-silicate rocks and amphybolites at NE. The structural control results from three successive deformation phases. Urban expansion and road construction, during the last 30 years, have strongly impacted the areas: (I) Base of Quebra-Pé hill; (II) Jardim Britânia; (III) Morro Doce; (IV) Nova Anhangüera Park. A 5 th site was disfgured by earthworks. The Jardim Britânia area is partly discharacterized by earthflls; this however does not impede further protection actions. This framework allows to recommend authorities: (1) to permit immediate preservation of these areas; (2) to develop programs to build an integrated site for scientifc diffusion or an educational center for exhibition of rocks, ores and mineral samples; (3) to support the interest of some owners to preserve the area called Morro Doce, (4) to put forward a few proposals for educational use of the excavations, by production of feld guides on the historic sites. The alternatives will help keeping alive the memory of mining in the São Paulo State.
The Historical Jaraguá Gold Caves: What remains to be preserved?
Keywords: Geology; Gold; Heritage conservation; Mining; São roque group